2015
DOI: 10.18488/journal.2/2015.5.2/2.2.60.72
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelationship among Locus of Control, Sexual Satisfaction and Marital Satisfaction

Abstract: The primary goal of the present study is to examine the interrelationships among locus of control, sexual satisfaction and marital satisfaction. In the current study, a sample which was composed of 200 married persons was investigated. Research tools include locus of control, sexual satisfaction and marital satisfaction. For data analysis, correlation and independent hierarchical multiple regression analyses were used to determine the relationships between the predictor variables and criterion variable. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…These findings suggest that sexual satisfaction is a very strong predictor of marriage quality. This is in line with Asgharianji et al (2015) who maintain that lack of sexual satisfaction in a marriage may bring negative consequences to the relationship between a wife and a husband. Female nurses without a fixed working schedule, especially those whose husbands also work and who experience a high level of stress at their workplaces, tend to have a very limited amount of time to spend with their respective partners (Hestya et al, 2012;NIOSH, 2008).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These findings suggest that sexual satisfaction is a very strong predictor of marriage quality. This is in line with Asgharianji et al (2015) who maintain that lack of sexual satisfaction in a marriage may bring negative consequences to the relationship between a wife and a husband. Female nurses without a fixed working schedule, especially those whose husbands also work and who experience a high level of stress at their workplaces, tend to have a very limited amount of time to spend with their respective partners (Hestya et al, 2012;NIOSH, 2008).…”
Section: Resultssupporting
confidence: 86%
“…One of the strongest predictors of marriage stability and spousal relationship quality is sexual satisfaction achieved through the relationship (Asgharianji et al, 2015). In spite of the importance of this factor, not much research has been done to investigate the correlation between sexual satisfaction and marriage quality, especially amongst female nurses.…”
Section: Introductionmentioning
confidence: 99%
“…However, before this, [34] asserted in his work that external locus of control was linked with higher marital change compared to the people with internal locus of control. The work of [31] revealed a similar pattern of results indicating that there is a substantial interrelationship between internal locus of control and marital satisfaction.…”
Section: Locus Of Control and Marital Satisfactionmentioning
confidence: 66%
“…Contemporary studies of the locus of control literature showed an increasing number of studies on the relationship between the type of control (internal and external) marriage [31], [32]. According to [33], locus of control as assessed in middle adulthood predicted marital satisfaction assessed contemporaneously.…”
Section: Locus Of Control and Marital Satisfactionmentioning
confidence: 99%
“…Locus of control and marital satisfaction: Contemporary studies of the locus of control literature showed an increasing number of studies on the relationship between the type of control (internal and external) in marriage [28,29] . According to Kahler [30] , locus of control as assessed in middle adulthood predicted marital satisfaction assessed contemporaneously.…”
Section: Introductionmentioning
confidence: 99%